Solid waste disposal comparison between open dumping and sanitary landfill (Kg. Pertok Machang, Kelantan (open dumping) and Puchong, Selangor (sanitary landfill) / Mohd Budiman Putra Hassan - Hassan, Mohd Budiman Putra (2003)
Humans and animals have used the resources of the earth to support life and to dispose of wastes. In early times, the disposal of solid wastes did not pose a significant problem, for the population was small and the amount of land available for the assimilation of wastes was large. Ecological phenomena such as air pollution, water pollution and land pollution have been attributed to improper management of solid waste. The aim of this dissertation is to provide a basic understanding of sanitary landfill and open dumping related issues. Both theory and legislation on the subject are included. Thus, this dissertation is to make a comparison between open dumping system at Kg. Pertok, Machang and sanitary landfill system at Air Hitam, Puchong. Other than that, to study and make a conclusion as to how the differences can occur as well as to identify the main sources of problem that is affecting the residential areas. From the analysis, there are four main factors that have influenced the disposal site in study areas. The factors that encourage of disposal site are system use, legislation, services and financial. However, disposal site have given variety of implication such as air pollution, water pollution, land pollution, health problem and other implications.